THE EFFECT OF LIFESTYLE ADVICE AND INTERVENTIONS FOR CARDIOVASCULAR RISK REDUCTION : A COMPREHENSIVE SYSTEMATIC REVIEW - Nuryanto, Heri; Venessa Paputungan, Tiara (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The risk of cardiovascular disease (CVD) in general and coronary heart disease in particular is significantly influenced by daily behaviors and actions.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 217 articles, whereas the results of our search on SAGEPUB brought up 3898 articles, our search on SCIENCE DIRECT brought up 10195 articles. The results of the search conducted for the last year of 2014 yielded a total 107 articles for PubMed, 1992 articles for SAGEPUB and 5649 articles for SCIENCE DIRECT. In the end, we compiled a total of 7 papers, 4 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included seven research that met the criteria.Conclusion: In summary, daily behaviors and habits have a significant impact on the risk of CVD. The major strategies that reduce the risk of CVD and improve quality of life include stress reduction, increased physical activity, healthy diet, weight control, and abstinence from tobacco.